Analysis of Laws for the Protection of Indonesian Migrant Workers Abroad - Wita Purnamasari; Evita Isretno Israhandi; Megawati Barthos (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
The situation of TKI abroad during the last few years has been very concerning and has received little attention from the government, the problem of TKI is considered less important and the government has only been busy talking when cases surfaced in the community and received negative responses from the community. Quoted from Republika.co.id Domestic violence (KDRT) among Indonesian citizens living in Australia has increased recently. Legal protection for female workers abroad who are victims of exploitation-rape currently prioritizes the fulfillment of the rights of victims who work legally abroad. The rights of all migrant workers and their families, as well as ILO conventions beforehand, contain elements to protect workers from Indonesia when they encounter a legal challenge in the host country of migrant workers. In addition, guidance is carried out by the government through BNP2TKI and BP3TKI by Article 90 of Law No. 39 of 2004 concerning the Placement and Protection of Overseas Workers, such as providing guidance and advocacy for TKI starting from pre-placement, placement, and post-placement periods. TKI understand the legal system of the TKI receiving country so that if the TKI encounter legal problems, they will know what to do. And also the activeness of ambassadors, consular officers, and attaches in establishing cooperation related to the protection of Indonesian workers who are victims in countries receiving TKI in various forms of diplomatic relations and MoUs